Are Self-Drilling, Self-Tapping Screws Effective in Anterior Cervical Fusion Surgery? One Surgeon’s Experience with 50 Consecutive Patients - Nikhil Dholaria; Juan P. Giraldo; Sohail Daulat; James Kelbert; Vick S. Sahni; Giovanni Barbagli; Christina Cannata; Diego T. Soto Rubio; Annemarie Pico; Amna Hussein; Abdullah Al-Arfaj; Michael Prim; et al. (Journal of Spine Practice, 2025)
Purpose